Strength Behaviors of Remolded Hydrate-Bearing Marine Sediments in Different Drilling Depths of the South China Sea - Yanghui Li; Tingting Luo; Xiang Sun; Weiguo Liu; Qingping Li; Yuanping Li; Yongchen Song (Energies, 2019)
The mechanical behaviors of hydrate-bearing marine sediments (HBMS) drilled from the seafloor need to be understood in order to safely exploit natural gas from marine hydrate reservoirs. In this study, hydrates were prepared using ice powder and CH4 gas, and HBMS from the Shenhu area in the South China Sea were remolded using a mixed sample preparation method. A series of triaxial tests were conducted on the remolded HBMS to investigate the effects of soil particle gradation and the existence of hydrate on the mechanical properties of hydrate reservoirs. The results show that the stiffness and failure strength of HBMS decrease along with the decrease of mean particle size and soil aggregate morphology change at different drilling depths, and the reduction of failure strength is more than 20% when the drilling depth drops by 30 m. A better particle gradation of marine sediments may boost the stiffness and failure strength of HBMS. In addition, the existence of hydrate plays an important role in the strength behaviors of HBMS. The reduction of failure strength of HBMS with 30% initial hydrate saturation is more than 35% after complete hydrate dissociation.